Analisis Throughput Varian TCP Pada Model Jaringan WiMAX - Medi Taruk; Ahmad Ashari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
Transmission Control Protocol (TCP) is a protocol that works at the transport layer of the OSI model. TCP was originally designed more destined for a wired network. However, to meet the need for the development of a very fast network technology based on the needs of the use by the user, it needs further development to the use of TCP on wireless devices. One implementation of a wireless network based on Worldwide Interoperability for Microwave Access (WiMAX) network is a model that offers a variety advantage, particularly in terms of access speed.In this case, use NS-2 to see throughput at TCP variants tested, namely TCP-Tahoe, TCP-Reno, TCP-Vegas, and TCP-SACK over WiMAX network model, with few observations scenarios. The first is a look at each of these variants throughput of TCP when only one particular variant of the work in the network. Second observe all variants of TCP throughput at the same time and have the equivalent QoS, but with the possibility of a small congestion based on the capacity of the link is made sufficient. Third observed throughput with multi congestion.In WiMAX network has scheduling services are UGS, rtPS and ertPS using UDP protocol and nrtPS and BE using the TCP Protocol. By using the software network simulator (NS-2) to obtain performance comparison TCP protocol-based services on the WiMAX network with QoS parameters are throughput, packet loss, fairness and time delay.